New Perspectives on Ibn ʻAsākir in Islamic Historiography - Judd, Steven C.; Scheiner, Jens J. (Brill, 2017)
This volume contains six articles on Ibn 'Asākir and his 'Ta'rīkh madīnat Dimāshq' illustrating a variety of perspectives and approaches to the material. It includes a seventh article that discusses the process by which the now standard 'Dār al-fikr' edition was compiled. The contributions address both the geographical and biographical sections of the 'Ta'rīkh madīnat Dimashq'. Some of the authors examine Ibn 'Asākir's sources, while others describe how Ibn 'Asākir's works were used by later generations of scholars and how he influenced multiple genres of later writings. The volume also contains analyses of individual biographies and discussions of Ibn 'Asākir's treatment of larger classes of people, including the first analysis of his biographies of women. In sum, it illustrates both the wide range of topics that the 'Ta'rīkh madīnat Dimashq' covers and the latest techniques for analyzing Ibn 'Asākir and his work.
Keywords: Historiography; Ibn ʻAsākir; ʻAlī ibn al-Ḥasan; 1105-1176. Tārīkh madīnat Dimashq; Islamic Empire; dept.his; faculty_collection

This City Belongs to You: A History of Student Activism in Guatemala, 1944-1996 - Vrana, Heather A. (University of California Press, 2017)
"Between 1944 and 1996, Guatemala experienced a revolution, counterrevolution, and civil war. In the middle of these national shifts were students from Guatemala's only public university, the University of San Carlos (USAC). USAC students served in, advised, protested, and were later persecuted by the government, all the while crafting a powerful student nationalism founded on their responsibility to lead the nation. In no other moment has the relationship between the university and the state been so mutable, yet so mutually formative. By showing how the very notion of the middle class in Guatemala emerged from these student movements, this book places an often-marginalized region and period at the center of histories of class, protest, and youth movements, while providing an entirely new way to think about the role of universities and student bodies in the formation of liberal democracy throughout Latin America.
Keywords: 20th century; Guatemala; History; Student movements; dept.his; faculty_collection

The lands of orthodoxy in the seventeenth century circa 1590-1720 - Bushkovitch, P.; Chrissidis, N.A.; Pǎun, R.G. (Cahiers du Monde Russe, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.his

Signum meum apposui: Notaries and their signs in medieval languedoc - Friedlander, A. (The Experience of Power in Medieval Europe, 950-1350, 2017)
Journal Abbreviation: The Exp. of Power in Mediev. Eur., 950-1350
Keywords: dept.his

Confucius and filial piety - Radice, Thomas (A Concise Companion to Confucius, 2017)
Keywords: dept.his

Dreams of antiquity: H. P. Lovecraft’s great Roman dream of 1927 - Nakamura, Byron (Lovecraftian Proceedings No. 2, 2017)
This second volume of Lovecraftian Proceedings contains a wealth of cutting-edge scholarship on the dreamer from Providence, including substantial articles from both recipients of the S. T. Joshi Endowed Research Fellowship for H. P. Lovecraft at Brown University. Lovecraftian Proceedings fosters exploration of Lovecraft as a rationalist who created an elaborate cosmic mythology, and how this mythology was influenced by, and has come to influence, numerous other authors and artists. The papers which comprise Lovecraftian Proceedings were presented during a key part of the NecronomiCon Providence convention, the Dr. Henry Armitage Memorial Symposium. TABLE OF CONTENTS Introduction Dennis P. Quinn Dreams of Antiquity: H. P. Lovecraft's Great Roman Dream of 1927Byron Nakamura The Poet’s Nightmare: The Nature of Things According to LovecraftSean Moreland Reordering the Universe: H. P. Lovecraft’s Subversion of the Biblical DivineRené J. Weise Resisting Cthulhu: Milton and Lovecraft’s Errand in the Wilderness Marcello Ricciardi “The Discriminating Urban Landscapist": Tradition and Innovation in the Architectural Writings of H. P. LovecraftConnor Pitetti Tentacles in the Madhouse: The Role of the Asylum in the Fiction of H. P. LovecraftTroy Rondinone Unspeakable Languages: Lovecraft Editions in Spanish Juan L. Pérez-de-Luque Color out of Mind: Correlating the Cthulhu Mythos Universe to the Autism Disorder SpectrumLars G. Backstrom Darwin and the Deep Ones: Anthropological Anxiety in "The Shadow over Innsmouth" and Other StoriesJeffrey Shanks The “Inside” of H. P. Lovecraft’s Supernatural Horror in the Visual Arts Nathaniel R. Wallace H. P. Lovecraft’s OptimismMatthew Beach Insider, Outsider: From the Commonplace to the Uncanny in H. P. Lovecraft’s Narration and DescriptionsDaphnée Tasia Bourdages-Athanassiou H. P. Lovecraft, Georges Bataille, and the Fascination of the Formless: One Crawling Chaos Seen Emerging from Opposite ShoresChristian Roy Ripples from Carcosa: H. P. Lovecraft, True Detective, and the Artist-InvestigatorHeather Poirier Lovecraft for the Little Ones: ParaNorman, Plushies, and MoreFaye Ringel and Jenna Randall Contributors AppendixAbstracts of Papers Presented at the Dr. Henry Armitage Memorial Scholarship Symposium,NecronomiCon Providence 20-23 August, 2015Chair: Dennis P. Quinn Index
Keywords: dept.his

Li (ritual) in early Confucianism - Radice, Thomas (Philosophy Compass, 2017)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-883-856-156-766, pop00371 tex.type: [object Object]
Keywords: dept.his

The implications of gia truyền: Family transmission texts, medical authors, and social class within the healing community in Vietnam - Thompson, C. Michele (South East Asia Research, 2017)
In Vietnamese medicine, gia truyen ("family recipes") refers to a set of texts, primarily in chu nôm (demotic Vietnamese characters), that preserves local knowledge about how practitioners in a specific family-based medical circle could use various plants and other materia medica to cure disease. This article traces the history of the transmission of gia truyen in the 19th and 20th centuries. It suggests that prior to the 1920s, gia truyen were written anonymously to protect the author's identity in the face of the Nguyen dynasty's repression of ch? nom writing. In the 1920s, precisely at the time that hán-nôm writing was being eclipsed by education in French and quoc ngu (Romanized Vietnamese), Vietnamese medical practitioners experienced a renaissance in the writing of chu nôm gia truyen. Moreover, chu nôm writing in the gia truyen genre continued until at least the 1990s. ©SOAS University of London 2017.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-172-230-163-181, pop00329 tex.type: [object Object]
Keywords: Chu nom; Colonial; Materia medica; Medical texts; Traditional medicine; Viet Nam; class; dept.his; disease treatment; historical perspective; medical geography; nineteenth century; social history; traditional knowledge; traditional medicine; twentieth century

Method mourning: Xunzi on ritual performance - Radice, Thomas (Philosophy East and West, 2017)
3 citations (Crossref) [2023-10-31]
Keywords: dept.his

The journey from discovery to scientific change: scientific communities, shared models, and specialised vocabulary - Roe, Sarah M (International Studies in the Philosophy of Science, 2017)
Scientific communities as social groupings and the role that such communities play in scientific change and the production of scientific knowledge is currently under debate. I examine theory change as a complex social interaction among individual scientists and the scientific community, and argue that individuals will be motivated to adopt a more radical or innovative attitude when confronted with striking similarities between model systems and a more robust understanding of specialised vocabulary. Two case studies from the biological sciences, Barbara McClintock and Stanley Prusiner, help motivate the idea that sharing of models and specialised vocabulary fill the gap between discovery and scientific change by promoting the dispersal of important information throughout the scientific community. © 2017 Open Society Foundation.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-085-635-391-358 tex.type: [object Object]
Keywords: dept.his

Extended mechanistic explanations: expanding the current mechanistic conception to include more complex biological systems - Roe, Sarah M; Baumgaertner, Bert (Journal for General Philosophy of Science, 2017)
Mechanistic accounts of explanation have recently found popularity within philosophy of science. Presently, we introduce the idea of an extended mechanistic explanation, which makes explicit room for the role of environment in explanation. After delineating Craver and Bechtel’s (2007) account, we argue this suggestion is not sufficiently robust when we take seriously the mechanistic environment and modeling practices involved in studying contemporary complex biological systems. Our goal is to extend the already profitable mechanistic picture by pointing out the importance of the mechanistic environment. It is our belief that extended mechanistic explanations, or mechanisms that take into consideration the temporal sequencing of the interplay between the mechanism and the environment, allow for mechanistic explanations regarding a broader group of scientific phenomena. © 2016, Springer Science+Business Media Dordrecht.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/167-521-013-773-230 tex.type: [object Object]
Keywords: Complex systems; Explanation; Mechanism; Mechanistic environment; dept.his